Diffusive random laser modes under a spatiotemporal scope - Garcia-Revilla, Sara; Fernandez, Joaquin; Barredo-Zuriarrain, Macarena; Carlos, Luis D.; Pecoraro, Edison [UNESP]; Iparraguirre, Ignacio; Azkargorta, Jon; Balda, Rolindes (Optical Soc Amer, 2015)
At present the prediction and characterization of the emission output of a diffusive random laser remains a challenge, despite the variety of investigated materials and theoretical interpretations given up to now. Here, a new mode selection method, based on spatial filtering and ultrafast detection, which allows to separate individual lasing modes and follow their temporal evolution is presented. In particular, the work explores the random laser behavior of a ground powder of an organic-inorganic hybrid compound based on Rhodamine B incorporated into a di-ureasil host. The experimental approach gives direct access to the mode structure and dynamics, shows clear modal relaxation oscillations, and illustrates the lasing modes stochastic behavior of this diffusive scattering system. The effect of the excitation energy on its modal density is also investigated. Finally, imaging measurements reveal the dominant role of diffusion over amplification processes in this kind of unconventional lasers. (C) 2015 Optical Society of America